THE DECOY EFFECT IN CONSUMER BEHAVIOR - Rahayu Lestari; Suadi Sapta Putra; Resti Hardini; Kumba Digdowiseiso; Azlinzuraini Ahmad (PT. Radja Intercontinental Publishing, 2024)
The objective of this study is to investigate and assess the influence of the Decoy effect on consumer behavior. This study focuses on the significance of comprehending the psychological elements that impact consumer buying choices, particularly through the influence of the teaser effect. The employed approach involves a Systematic Literature Review (SLR), which entails conducting a methodical and thorough search of existing literature to identify the most recent discoveries pertaining to the Decoy effect and consumer behavior. The research findings and subsequent analysis emphasize that the Decoy effect has the ability to impact consumer preferences and marketing strategies. However, it also carries the potential for manipulation and the implementation of unfair pricing policies. Evidence from the literature affirms the necessity for companies to adopt marketing strategies that prioritize ethics, transparency, and honesty in order to uphold consumer trust. The research concludes that a thorough comprehension of consumer behavior and strategic utilization of the Decoy effect is crucial for attaining favorable outcomes and mitigating potential drawbacks. Hence, this study offers valuable perspectives for businesses to create more efficient and morally sound marketing tactics within the realm of consumer behavior.